The distribution of power and household behavior: Evidence from Niger - Wouterse, Fleur Stephanie (International Food Policy Research Institute, 2016)
Niger is a landlocked Sahelian country, two-thirds of which is in the Sahara desert. Although only one-eighth of the land considered arable, more than 90 percent of Niger’s labor force is employed in agriculture, which is predominantly subsistence oriented. Food security remains a major challenge in rural areas of Niger, and gender is a significant basis for the inequality among household members with respect to access to land. Access to land, which is a measure of the income-earning potential of an individual, is an important determinant of the distribution of bargaining power within the household. Because households may not act in a unitary manner when making decisions, the power of individuals within the household to exert their own preferences may determine welfare outcomes, such as spending on nutritious foods or healthcare. In this paper, we use new data for Niger and regression analyses to assess the importance of the intrahousehold distribution of power for the behavior of rural households. Our results reveal that men are significantly more empowered than women in rural households in Niger and that social protection programs such as water, sanitation, and hygiene (WASH) and food-for-training contribute significantly to the empowerment of women. Our findings also point to the validity of the collective approach to modeling household behavior, as the distribution of power was shown to affect household behavior. In particular, we found that an increase in power in favor of the adult female significantly increases expenditures on healthcare and reduces spending on vices (cigarettes and alcohol).